2017
DOI: 10.1074/jbc.m116.766725
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Allosteric Inhibition of Brain Glycogen Phosphorylase by Neurotoxic Dithiocarbamate Chemicals

Abstract: Edited by Ruma BanerjeeDithiocarbamates (DTCs) are important industrial chemicals used extensively as pesticides and in a variety of therapeutic applications. However, they have also been associated with neurotoxic effects and in particular with the development of Parkinson-like neuropathy. Although different pathways and enzymes (such as ubiquitin ligases or the proteasome) have been identified as potential targets of DTCs in the brain, the molecular mechanisms underlying their neurotoxicity remain poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…So far, a limited number of enzymes have been reported to be inhibited by Thiram (Lippmann and Lloyd, 1969; Caroldi De Paris, 1995;Atanasov et al, 2003;Garbrecht et al, 2006;van Boxtel et al, 2010;Mathieu et al, 2017). In addition to these enzymes, our data show that Thiram is also able to inhibit a phase II xenobiotic-metabolizing enzyme known to play a major role in the metabolism of arylamine xenobiotics.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…So far, a limited number of enzymes have been reported to be inhibited by Thiram (Lippmann and Lloyd, 1969; Caroldi De Paris, 1995;Atanasov et al, 2003;Garbrecht et al, 2006;van Boxtel et al, 2010;Mathieu et al, 2017). In addition to these enzymes, our data show that Thiram is also able to inhibit a phase II xenobiotic-metabolizing enzyme known to play a major role in the metabolism of arylamine xenobiotics.…”
Section: Discussionmentioning
confidence: 49%
“…Certain metabolites of DTCs (such as sulfoxide or sulfone forms) are also reactive. The toxic effects of DTC are thus thought to be due to the parent compounds and their metabolites (Jin et al, 1994;Staub et al, 1998;Mathieu et al, 2015Mathieu et al, , 2017. So far, Thiram pesticide has been clearly shown to impair the activity of few enzymes, i.e., dopamine b-hydroxylase, 11b-hydroxysteroid dehydrogenase, lysyl oxidase, and brain glycogen phosphorylase (Lippmann and Lloyd, 1969;Caroldi and De Paris, 1995;Atanasov et al, 2003;Garbrecht et al, 2006;van Boxtel et al, 2010;Mathieu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that impairments in carbohydrate metabolism in the brain are associated with ASD [ 71 , 74 ]. It is within reason that this study implicates carbohydrate metabolism in ASD’s etiology, considering that some pesticides exact their neurotoxic effects by targeting carbohydrate metabolism [ 75 , 76 ]. FXR/RXR activation and Type I Diabetes Mellitus ( Table 3 ) are two pathways identified here that support this carbohydrate metabolism hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mathieu et al showed that thiram,aneurotoxic disulfide-containingd ithiocarbamate compoundi nhibits brain glycogenp hosphorylase through the formationo fa ni ntramolecular disulfide bond between Cys 318 and Cys 326 ,k nown to be ar edox-switch that prevents the allosteric activation of the enzyme by AMP. [22,23] The proposed mechanism consistso ft he reactiono ft hiram with ac ysteinet hiol leading to am ixed disulfide followedby the formation of an intramolecular disulfide bond with av icinal cysteiner esidue. Another example describes the inactivationo fa na rginine phosphatase by as eleno-compoundt hat induces an intramolecular disulfide bond betweent wo adjacent actives ite cysteinesv ia an unclear mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Mathieu et al. showed that thiram, a neurotoxic disulfide‐containing dithiocarbamate compound inhibits brain glycogen phosphorylase through the formation of an intramolecular disulfide bond between Cys 318 and Cys 326 , known to be a redox‐switch that prevents the allosteric activation of the enzyme by AMP . The proposed mechanism consists of the reaction of thiram with a cysteine thiol leading to a mixed disulfide followed by the formation of an intramolecular disulfide bond with a vicinal cysteine residue.…”
Section: Introductionmentioning
confidence: 99%